Diabetes insipidus in neuropsychiatric-systemic lupus erythematosus patient - Y Pangestu; A Wardoyo; Linda K Wijaya; BAMBANG SETIYOHADI; Zuljasri Albar; N Sukmana; Budiman Budiman; Z Djoerban; S Effendy; L Aziza; F Sitorus (Indonesian Rheumatology Association, 2009)
Systemic lupus erythematosus (SLE) is an idiopathic autoimmune chronic inflammatorydisease that is unique in its diversity of clinical manifestations, variability of diseaseâ€™s progression, and prognosis. The disease is characterized by the remission and multiple flare-ups in between the chronic phase that may affect many organ systems.The prevalence of SLE in the US population is 1:1000 with a woman to man ratio of about 9-14:1. At Cipto Mangunkusumo Hospital, Jakarta in 2002, there was 1.4% cases of SLE of the total number of patients at the Rheumatology Clinic. Neuropsychiatric manifestations of SLE (NP-SLE) have a high mortality and morbidity rates. The incidence of NP-SLE ranges 18-61%. Diagnosis of NP-SLE is difficult because there is no specific laboratory examination. Accordingly, in all SLE patients with central nervous system (CNS) dysfunction, additional tests will be necessary to confirm an NP-SLE diagnosis and exclude other causes.Â Similar to diabetes insipidus, SLE is a systemic disease which affects many organ systems, one being the endocrine system. No data has specified the occurrence rate of diabetes insipidus in SLE patients. This disease arises from a number of factors able to interfere with the mechanism of neurohypophyseal renal reflex resulting in the bodyâ€™s failure to convert water.3 There are three general forms of the disease, a polydipsicpolyuric syndrome caused by partial/complete vasopressin deficiency (central-diabetes-insipidus/CDI), vasopressin resistance of the kidney tubules (nephrogenic-diabetes-insipidus/NDI), and primary polydipsia. CDI occurs in about 1 in 25,000 persons